Answer:
The correct answer is x = 6.
Step-by-step explanation:
To solve this problem, we first must recognize that DE + EF = DF.
From this information, we can set up the following equation when we substitute in the given values:
DE + EF = DF
(4x-1) + 9 = 9x - 22
Our first step is going to be to combine like terms on the left side of the equation. This is modeled below:
4x - 1 + 9 = 9x - 22
4x + 8 = 9x - 22
Then, we should subtract 4x from both sides of the equation.
8 = 5x - 22
Now, we can add 22 to both sides of the equation.
30 = 5x
Finally, we can divide both sides by 5.
x = 6
Therefore, the correct answer is x = 6.
Hope this helps!
Answer: 9-3x
Step-by-step explanation:
You add like terms
don't look at the 3x for now
positive 7 + positive 2 = 9
there is a negative sign next to 3x
9 goes first so
9 - 3x
Answer:
right 2 , up 3.
Step-by-step explanation:
The -2 moves 2 to the right and the + 3 means 3 up.
Answer:
Step-by-step explanation:
A.
R(x)=px=x(-45 x+1800)=-45 x²+1800 x
B.
C(x)=7000+100 x
C.
P(x)=R(x)-C(x)=-45 x²+1800 x-(7000+100 x)
or P(x)=-45x²+1800 x-100 x-7000
or P(x)=-45 x²+1700 x-7000
Ratio being 12in./1ft.
3 inches is not one foot. it's 1/4 of a foot. 3in./1/4ft.
3 feet = 36 inches.
36in./3ft.
Hope This Helped! Good Luck!